Cellulose filtration of blood from malaria patients for improving ex vivo growth of Plasmodium falciparum parasites. (December 2017) - Mkumbaye, Sixbert; Minja, Daniel; Jespersen, Jakob; Alifrangis, Michael; Kavishe, Reginald; Mwakalinga, Steven; Lusingu, John; Theander, Thor; Lavstsen, Thomas; Wang, Christian
Abstract Background Establishing in vitroPlasmodium falciparum culture lines from patient parasite isolates can offer deeper understanding of geographic variations of drug sensitivity and mechanisms of malaria pathogenesis and immunity. Cellulose column filtration of blood is an inexpensive, rapid and effective method for the removal of host factors, such as leucocytes and platelets, significantly improving the purification of parasite DNA in a blood sample. Methods In this study, the effect of cellulose column filtration of venous blood on the initial in vitro growth ofP. falciparum parasite isolates from Tanzanian children admitted to hospital was tested. The parasites were allowed to expand in culture without subcultivation until 5 days after admission or the appearance of dead parasites and parasitaemia was determined daily. To investigate whether the filtration had an effect on clonality, P. falciparum merozoite surface protein 2 genotyping was performed using nested PCR on extracted genomic DNA, and thevar gene transcript levels were investigated, using quantitative PCR on extracted RNA, at admission and 4 days of culture. Results The cellulose-filtered parasites grew to higher parasitaemia faster than non-filtered parasites seemingly due to a higher development ratio of ring stage parasites progressing into the late stages. Cellulose filtration had no apparent effect on clonality orvar gene expression; however, evident differences were observed after only 4 days of culture in both the number of clones and transcript levels ofvar genes compared to the time of admission. Conclusions Cellulose column filtration of parasitized blood is a cheap, applicable method for improving cultivation ofP. falciparum field isolates for ex vivo based assays; however, when assessing phenotype and genotype of cultured parasites, in general, assumed to represent the in vivo infection, caution is advised.